2016
DOI: 10.18632/oncotarget.8615
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin is involved in promotion of colorectal carcinoma malignancy through an inducing EMT mechanism

Abstract: Increasing evidences suggested visfatin, a newly discovered obesity-induced adipocytokine, is involved in promotion of cancer malignancy and correlated with worse clinical prognosis. While its effects and mechanisms on progression of colorectal cancer (CRC) remain unclear. Our clinical data show that visfatin protein is over expressed, positive associated with lymph node metastasis, high-grade tumor, and poor prognosis in 87 CRC patients. The levels of plasma visfatin are significantly upregulated in Stage IV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…Similar associations between serum visfatin and clinical pathologic variables were observed in breast cancer patients along with regulation of MDA-MB-231 cell migration and invasion capabilities via c-Abl and STAT3 activation 16. The induction of the epithelial–mesenchymal transition process by visfatin was investigated in CRC, and the results indicated that visfatin could upregulate Snail in CRC cells by activating Akt/GSK-3β/β-catenin signaling 15. Furthermore, visfatin was found to significantly increase the in vitro migration and invasion capability of osteosarcoma MG-63 and HOS cells, and to upregulate MMP-2 and fibronectin expression through the NF- B/IL-6 signaling axis 46.…”
Section: Visfatin and Metastasismentioning
confidence: 55%
See 1 more Smart Citation
“…Similar associations between serum visfatin and clinical pathologic variables were observed in breast cancer patients along with regulation of MDA-MB-231 cell migration and invasion capabilities via c-Abl and STAT3 activation 16. The induction of the epithelial–mesenchymal transition process by visfatin was investigated in CRC, and the results indicated that visfatin could upregulate Snail in CRC cells by activating Akt/GSK-3β/β-catenin signaling 15. Furthermore, visfatin was found to significantly increase the in vitro migration and invasion capability of osteosarcoma MG-63 and HOS cells, and to upregulate MMP-2 and fibronectin expression through the NF- B/IL-6 signaling axis 46.…”
Section: Visfatin and Metastasismentioning
confidence: 55%
“…In addition, hepatocellular carcinoma patients with high serum visfatin levels had shorter overall survival times compared with those with low serum visfatin levels ( p <0.001) 14. In colorectal carcinoma cases, the results of a Kaplan–Meier analysis of 87 patients indicated a statistically negative correlation between visfatin levels and overall survival probability ( p <0.001) 15. A study of 176 breast cancer biopsy tissues demonstrated that visfatin is a prognosis marker for its association with poor patient survival 8.…”
Section: Correlation With Clinical Outcomementioning
confidence: 97%
“…Zhao et al [ 17 ] found that ING5 significantly inhibited the phosphorylation of PI3K and Akt in breast cancer cells, leading to MET. In addition, EMT is positively associated with aberrant activation of Wnt or the PI3K/Akt pathway, which activates GSK-3β and stabilizes β-catenin [ 20 , 21 ]. We found that PI3K, Akt, and β-catenin were decreased in ING5 transfectants of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, differentiation of fibroblasts into myofibroblasts is a reversible process, giving a potential possibility to invert it and find new drugs attenuating fibrosis [ 129 ]. It was proved that many adipokines, especially visfatin and progranuline are involved in the process of EMT, which is a transition akin to AMT process [ 21 , 128 ].…”
Section: Adipose Tissue In Systemic Sclerosismentioning
confidence: 99%